Observation of CP violation in charm decays - Aaij, R; Abellán Beteta, C; Adeva, B; Bjørn, M; Gruberg Cazon, BR; Hadavizadeh, T; Hancock, TH; Harnew, N; Hill, D; Jalocha, J; John, M; Jurik, N; et al. (American Physical Society, 2019)
A search for charge-parity (CP) violation in D0→K−K+ and D0→π−π+ decays is reported, using pp collision data corresponding to an integrated luminosity of 5.9 fb−1 collected at a center-of-mass energy of 13 TeV with the LHCb detector. The flavor of the charm meson is inferred from the charge of the pion in D∗(2010)+→D0π+ decays or from the charge of the muon in ¯B→D0μ−¯νμX decays. The difference between the CP asymmetries in D0→K−K+ and D0→π−π+ decays is measured to be ΔACP=[−18.2±3.2(stat)±0.9(syst)]×10−4 for π-tagged and ΔACP=[−9±8(stat)±5(syst)]×10−4 for μ-tagged D0 mesons. Combining these with previous LHCb results leads to ΔACP=(−15.4±2.9)×10−4, where the uncertainty includes both statistical and systematic contributions. The measured value differs from zero by more than 5 standard deviations. This is the first observation of CP violation in the decay of charm hadrons.